Nov pripomoček pri prevajalskem delu: računalniški korpusi - Hirci, Nataša (Mostovi (Ljubljana), 2001)
The article gives an outline of some applications of computer corpora for translation, and in a brief survey of the advantages and problems involved in using such translation tools.
Keywords: besedilni korpusi; prevajanje; prevodi; računalniški korpusi